2020
DOI: 10.1111/1440-1703.12184
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic effect of invasive speciesAmorpha fruticosaL. on germination and the early growth of forage and agricultural crop plants

Abstract: Invasive plant species can inhibit the growth of native plants by competing for resources as well as by secreting allelochemicals. Indigobush (Amorpha fruticosa L.), a deciduous shrub adaptable to a wide range of environmental conditions, was introduced into Europe as a decorative and valuable honey plant. In this study, we assayed the phytotoxic effect of aqueous leaf extracts (1, 3 and 5%) obtained from A. fruticosa leaves on seed germination and seedling growth of four important agricultural species (Trifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(56 reference statements)
0
5
1
Order By: Relevance
“…Similar to our findings, the germination and growth of the seedlings were significantly inhibited by the aqueous extract of false indigo-bush, with the strongest negative effect observed on shoot growth. Krstin et al [56] also characterized the phytotoxic effects of aqueous leaf extracts obtained from A. fruticosa (1%, 3%, and 5% concentrations) in an in vitro study on the germination and growth of four important agricultural species (Helianthus annuus L., Medicago sativa L., Trifolium pratense L., and Triticum aestivum L.). Similar to our findings, their results showed that the phytotoxicity of false indigo-bush leaf extract depended on its concentration, with higher concentrations exhibiting stronger phytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, the germination and growth of the seedlings were significantly inhibited by the aqueous extract of false indigo-bush, with the strongest negative effect observed on shoot growth. Krstin et al [56] also characterized the phytotoxic effects of aqueous leaf extracts obtained from A. fruticosa (1%, 3%, and 5% concentrations) in an in vitro study on the germination and growth of four important agricultural species (Helianthus annuus L., Medicago sativa L., Trifolium pratense L., and Triticum aestivum L.). Similar to our findings, their results showed that the phytotoxicity of false indigo-bush leaf extract depended on its concentration, with higher concentrations exhibiting stronger phytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is a difficult weed to control in floodplain afforestation, and arable land and grassland management. Due to its allelopathic substances, its rapid invasion of agricultural fields can negatively affect the growth and yield of valuable forage and agricultural crops [56]. It is also a serious problem from the perspective of flood control [57].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies compared the effects of the aqueous extracts to effects of known allelopathic compounds, which suggest that the effect of the aqueous extract is due to chemical inhibition (e.g. Krstin et al 2021). It has, however, also been suggested that the effect of the aqueous extracts is not always due to chemical inhibition but can be due to the high osmolality of the extracts (Inderjit and Nilsen 2003, Loydi et al 2015, Oduor et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the new weapon hypothesis verifies that numerous invasive plant species can incur evident allelopathic intensity by secreting several types of secondary substances and noxious compounds, i.e., allelochemicals, that can decrease the growth of native plants (Djurdjević et al 2012, Fabbro et al 2014, Lyytinen & Lindström 2019, Hsueh et al 2020. More importantly, the process of seed germination and seedling growth (SGe and SGr) was most obviously affected by the allelochemicals of invasive plant species at the beginning of their life history (Fabbro et al 2014, Wang et al 2017a, b, 2018c, d, 2019d, 2020c, Carvalhoa et al 2019, Hsueh et al 2020, Krstin et al 2021). However, SGe and SGr are critical to individual growth and the development of biomes.…”
Section: Introductionmentioning
confidence: 99%